Determining the Underlying Reasons of License Termination and Cancellation Associated with Local Power Production in Turkey - Toptas, Mehmet (International Journal of Energy Economics and Policy, 2015)
Considerable changes have taken place in power production investments in Turkey within the last decade. As a result, an increasing number of investments in this sector have been terminated or cancelled and still continue to do so. When these investments are analyzed, significant issues attributed to misconceptions on cash flow estimations, local community objections, changes in the Environmental Impact Assessment Regulation interpretations, diminished trust in the conducted project evaluations and the associated reduction of capital and funds have been observed. Thus, the main contributors and their underlying reasons for these issues are examined in this study. In order to determine the associated key aspects and parameters, a survey has been developed and distributed to companies working on the renewable energy sector with questions regarding the number and the size of the licenses they have, the percentage of them turning into investments, the major methods of financial evaluation they use in the decision making process, their ability to calculate the cash flows during project evaluation process and the modelling of associated risk factors in the renewable energy sector. Keywords: Project evaluation methods; power production; license termination; Turkey JEL Classifications: O220; O250; Q280